PENGARUH TENAGA KERJA WANITA TERHADAP EFISIENSI USAHATANI PADI SAWAH - Pika Shabirah; Harianto; Ahmad Suryana (JURNAL AGRIBISAINS, 2022)
Most of the women work in the informal sector, especially in the agricultural sector (61.80%), as well as the male workers (53.71%). This shows the high contibution and participation of women in agricultural activities.This study aimed to analyze the influence of female workers on the technical efficiency of lowland rice farming and to analyze the factors that influence it. This study used Translog Stochastic Frontier production function and was estimated using the Maximum Likelihood Estimation (MLE) method. The results showed that lowland rice farming, both with male-headed and female-headed household, was not technically efficient (0.617 and 0.598) with significantly different efficiency between male-headed household and female-headed household. The Ministry of Agriculture is advised to increase the intensity of agricultural extension to farmers related to rice farming techniques to further improve rice farming efficiency.Keywords: Female labor, Rice farming efficiency, Translog stochastic frontier